Problems of Income Disparity Based on the Gini Ratio in the Indonesian Economy - Frisnoiry, Suci; Febrianti, Dwi Ayu; Tambunan, Engeli Emmanuela Br; Tarigan, Gita Helena (PT FORMOSA CENDEKIA GLOBAL, 2024)
Income Disparity is a problem that is still being intensively discussed. This journal aims to provide more in-depth knowledge about the economic system and income disparities in Indonesia. The type of research methodology used is descriptive qualitative. The data used in the research is in the form of literature, news stories and books. The results of the discussion show that the factors causing income disparities include investment, Human Development Index (HDI), labor productivity, economic growth, natural resources, differences in demographic conditions and education levels. The impact of income disparities is extreme poverty, and also endangers social stability and economic growth. The proposed solution involves equal development, equal education levels, equal minimum wages, community empowerment and the Micro, Small and Medium Enterprises (MSME) sector.